Simultaneous synthesis and consolidation of nanostuctured MgAl2O4 compound by high-frequency induction heated sintering - Shon, In-Jin; Kwak, Seung-Mi; Doh, Jung-Mann; Park, Bang-Ju; Yoon, Jin-Kook (SPRINGER, 2013)
The rapid sintering of a nanostuctured MgAl2O4 compound in a short time was investigated with high-frequency induction heating sintering process. The advantage of this process is that it allows very quick densification to near theoretical density and prohibition of grain growth in nanostuctured materials. A highly dense nanostructured MgAl2O4 compound was produced with simultaneous application of 80 MPa pressure and induced current with output of total power capacity (15 kW) within 2 min. The sintering behavior, grain size, and mechanical properties of the MgAl2O4 compound were investigated.
Keywords: COMPOSITE